A Comparison of Psychological Response, Body Image, Sexuality, and Quality of Life between Immediate and Delayed Autologous Tissue Breast Reconstruction: A Prospective Long-Term Outcome Study. Issue 4 (October 2016) - Zhong, Toni; Hu, Jiayi; Bagher, Shaghayegh; Vo, Anthony; O'Neill, Anne C.; Butler, Kate; Novak, Christine B.; Hofer, Stefan O. P.; Metcalfe, Kelly A.
Abstract : Background: This is the first study to use generic distress, cancer-specific, and procedure-specific measures to prospectively evaluate psychological responses, body image, sexuality, and health-related quality of life in immediate compared with delayed breast reconstruction. Methods: Consecutive patients undergoing autologous immediate and delayed breast reconstruction (June of 2009 to December of 2010) completed the Hospital Anxiety and Depression Scale, Body Image Scale, Sexuality Scale, and BREAST-Q preoperatively and postoperatively (6, 12, and 18 months). Linear mixed-effects analyses between each outcome and time point were performed. Results: One hundred six women underwent mastectomy with immediate ( n = 30) and delayed breast reconstruction ( n = 76). Before reconstruction, 26 percent of patients had abnormal anxiety scores and 9 percent had abnormal depression scores, with no significant differences between groups. Patients awaiting delayed breast reconstruction had significantly impaired prereconstruction body image ( p = 0.01) and sexuality ( p = 0.01) and worse satisfaction with breast ( p < 0.01), psychological ( p < 0.01), and sexual well-being ( p < 0.01). At 18 months after immediate and delayed breast reconstruction, there was significant improvement in anxiety, depression, body image, sexuality, and health-related quality of life. Conclusions: This single-center study shows that mastectomy with immediate breast reconstruction may protect breast cancer patients from a period of psychosocial distress, poor body image, and diminished sexual well-being compared with those waiting for delayed breast reconstruction. In patients who are oncologically eligible and strongly interested in breast reconstruction, efforts should be made to provide immediate breast reconstruction to decrease the interval of psychosocial distress, poor body image, and impaired sexuality.